Effect of Alkyl Chain Length on Dissolution and Regeneration Behavior of Cotton in 1-Alkyl-3-methylimidazolium Acetate Ionic Liquids - Niwanthi Dissanayake; Vidura D. Thalangamaarachchige; Edward Quitevis; Noureddine Abidi (Molecules, 2025)
Ionic liquids (ILs) have attained considerable attention as cellulose solvents. Nevertheless, the detailed mechanism of cellulose dissolution in ILs is not clearly defined. It is crucial to recognize the role of the individual components of the ILs to fully understand this mechanism. During this study, the effect of alkyl chain length in imidazolium cation was examined using synthesized ILs which are composed of common acetate anion and imidazolium cations with different alkyl substituents. This study also aimed to investigate the odd–even effect of alkyl chain carbons. Furthermore, whereas most published investigations on cellulose dissolution in ILs used microcrystalline cellulose (MCC), which has a far lower degree of polymerization, in this study, cotton cellulose was used. During the dissolution experiments, cotton cellulose (5% w/w) was added to each IL, and the progress of the dissolution was monitored using polarized light microscopy (PLM). The regeneration of cellulose was performed by using water as the anti-solvent, and the regenerated cellulose was characterized by Fourier-transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). During these experiments, it was noted that ILs with odd C3 and C5 carbon chains were less effective at dissolving cellulose than those with even C2 and C4 alkyl chains. Additionally, after regeneration, biomaterials for a variety of applications could be produced.